IMPROVING LISTENING COMPREHENSION THROUGH STORYTELLING - PUJI HARIATI (LP2MTBM MAKARIOZ, 2019)
This study was aimed to find out the improvement of the students’ listening comprehension ability through storytelling. The study was conducted by using Classroom Action Research. It was done through 1) planning, 2) action, 3) observation, and 4) reflection. The location of the research was SMA Negeri 11 Medan. To get the sample of the research, the researcher took one class, it was class XI IPA1. This research applied quantitative and qualitative data. Quantitative data were taken from the students' listening comprehension test. Qualitative data were taken from questionnaires sheet. Based on the listening comprehension test scores, students’ score keep improving in every test. In the Pre-test the mean score was 31, in the first cycle test the mean score was 54,33, and in the second cycle test the mean score was 92,66. The improvement also can be seen from the percentage of students’ listening comprehension; in Pre-test no one of the students got 75 point, so got 0%. In first cycle test 10% (3 students) got 75 points. It means there was an improvement about 10%. In the second cycle test 100% (30 students) got 75 points. The improvement was 90%. It proved by the ability of the students score to answer the questions of the test. It means that teaching by using storytelling can improve students’ achievement in listening comprehension. The storytelling made the students feel comfortable, have fun, and new experience, and enjoyable